THE INFLUENCE OF MANAGERIAL COMPETENCE AND WORK MOTIVATION ON EMPLOYEE PRODUCTIVITY WITH TRAINING EXPERIENCE AS A MEDIATING VARIABLE AT PT RAY CHAIN SHOES INDONESIA - Mirzatus Safirah; Hadiah Fitriah (Antis Publisher, 2026)
Objective: This study aims to analyze the influence of managerial competence and work motivation on employee productivity with training experience as a mediating variable at PT Ray Chain Shoes Indonesia. Method: This study uses a quantitative approach with an explanatory survey method. The data used are primary data obtained through direct questionnaire distribution to 60 employees selected using a purposive sampling technique. The data analysis technique uses Structural Equation Modeling based on Partial Least Squares (SEM-PLS) with the help of SmartPLS software. Results: The results of the study indicate that managerial competence and work motivation have a positive and significant effect on employee productivity. In addition, managerial competence and work motivation also have a positive and significant effect on training experience. The R-Square value indicates that the research model has a strong ability to explain the dependent variable. Novelty: Training experience is proven to have a positive and significant effect on employee productivity and is able to mediate the influence of managerial competence and work motivation on employee productivity. This study provides implications that increasing employee productivity can be done through strengthening managerial competence, increasing work motivation, and implementing effective training programs. Therefore, companies are advised to develop integrated human resource management policies to improve employee performance and productivity sustainably.